Policy Toolkits on Employment and Ageing: A Conceptual Framework - Nata Duvvury; Jonas Radl; E. K. Sarter; Simone Scherger; Jeroen Spijker (Extended Working Life Policies. International Gender and Health Perspectives, 2020)
Policy toolkits provide useful information and can be drawn upon as guidance in different stages of the policy-making process. This chapter reviews existing policy toolkits on employment and ageing, aiming to distil a conceptual categorisation intended to inform research uptake strategies. As a basis, we develop a clear definition of policy toolkits and propose a typology of policy tools that consists of four types: (1) good practice, (2) social indicators, (3) programme evaluation and (4) forecasts, projections and simulations. We also describe the underlying relationship between research and policy-making, and provide a synthetic overview of toolkits available for ageing-related issues in the area of employment and pensions. We conclude with the observation that effective policy toolkits hinge on the prior formulation of clear policy goals and that different policy goals may not always be congruent with each other or be simultaneously achieved.
Keywords: 300; policy toolkits; policy cycle; programme evaluation; population ageing; extended working